Real-World Analysis of Remote Electrical Neuromodulation (REN) for the Acute Treatment of Migraine - Ailani, Jessica; Rabany, Liron; Tamir, Shira; Ironi, Alon; Starling, Amaal (Frontiers in Pain Research, 2022)
Abstract: Introduction: Migraine is a chronic neurological disease that is the primary cause of years lived with disability in people under the age of 50. Remote electrical neuromodulation (REN) is a novel drug-free acute treatment of migraine, that is FDA cleared for episodic and chronic migraine. As a prescribed digital therapeutic, REN enables large-scale post-marketing research, thus providing real-world information on the use of the intervention in a wide range of populations, environments, and situations. Methods: The REN device (® Nerivio) includes a secured, personal migraine diary, which patients can use to record their symptoms before treatment and 2 hours post-treatment. Real-world data on REN treatments were collected via the app from patients across the United States who used Nerivio between October 1st, 2019, and May 24th, 2021. Data analysis focused on four metrics: 1. Per-treatment patterns of REN use as a standalone treatment vs. in combination with medications. 2. Per-user intra-individual efficacy across multiple treatments. 3. Distribution of treatment intensity among users (the electroceutical equivalent to treatment dose). 4. Prevalence and severity of adverse events. Results: 1. Out of 23,151 treatments, in 66.5% of treatments REN was used as a standalone treatment, in 12.9% it was followed by over-the-counter medications, and in 20.6% followed by prescription medications. 2. Out of 2,514 patients, response in at least 50% of treatments was achieved in 66.5% of cases for pain relief, and in 20.9% for pain freedom. 3. Out of 117,583 treatments, in 80% of cases intensity levels were between 18% and 55% of the stimulator’s range. The mean intensity was 34.3% of the stimulator’s output (±16.6%). 4. Out of 12,368 users (121,947 treatments), there were 59 users (0.48%) who reported device related adverse events, 56 (0.45%) of which were mild, three (0.03%) were moderate, and none were severe. Conclusions: The current analysis of real-world clinical data indicates that REN provides an efficacious, stable, and safe treatment option for acute treatment of migraine in real-world settings, both as a standalone replacement of pharmaceuticals, as well as an adjunct to medications.